PENGARUH MOTIVASI BELAJAR MAHASISWA TERHADAP PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 TAHUN 2020 DENGAN METODE PARTIAL LEAST SQUARE (PLS) - Margie Christanty Poluan; Ignatia Rosali Honandar (Universitas Sam Ratulangi, 2023)
This study aims to measure how much influence student learning motivation has on the online learning process throughout 2020.The objects of this research are students of the accounting study program, Faculty of Economics, who are still actively participating in learning online during the pandemic with a total sample of 171 students selected by simple random sampling. Based on this amount that have 26% from first semester, 22.2% of third semester, 24% of fifth semester and 26.9% seventh semester. The collected data is processed and analyzed using SEM-PLS analysis assisted by SmartPLS software version 3.3.3. As for the interpretation of the data, namely the outer model test, inner model, and hypothesis testing, the research was carried out referring to Hair, et al. (2014) and Garson (2016) in Risa (2021).The results of this study indicate that students' learning motivation towards online learning has a positive and significant effect with the results of calculations using the assisted SEM-PLS method. SmartPLS software version 3.3.3 shows that the influence of motivation (X1) on online learning (Y1) is positive (0.801) and the significance is P Value < 0.05 (0.000 <0.05) and the t statistic value is 13,372 (13,372 > 1.96) (z value -score normal at = 0.05). According to Hair et al. (2014) in Risa (2021), the t-statistic value > normal z-score value indicates a significant effect. It is hoped that the results in the research can be useful for the faculty, especially the Accounting study program as an evaluation material for the online learning process. Keywords: Learning Management System, learning, online, application, motivation, new normal